2020
DOI: 10.21053/ceo.2019.01305
|View full text |Cite
|
Sign up to set email alerts
|

Navigation-Assisted Balloon Eustachian Tuboplasty for Eustachian Tube Dilatory Dysfunction

Abstract: Objectives. Balloon Eustachian tuboplasty (BET) is a novel treatment method for Eustachian tube dilatory dysfunction (ETD). However, surgeons cannot identify the insertion depth of the catheter during BET, resulting in potential risks such as internal carotid artery (ICA) injury. Therefore, we developed an image-guided navigation balloon catheter to identify the insertion depth of the catheter and to establish awareness of the proximity of the ICA. This study aimed to evaluate the technical feasibility of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Navigation-guided BET was technically successful and safely performed in all patients. During all the BET procedures, we were able to confirm the insertion depth of the catheter and establish awareness of the proximity of the internal carotid artery 15 . This prospective, multicenter, RCT study suggests that navigation-guided BET is a superior treatment option compared to MM alone in patients with chronic ETD.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Navigation-guided BET was technically successful and safely performed in all patients. During all the BET procedures, we were able to confirm the insertion depth of the catheter and establish awareness of the proximity of the internal carotid artery 15 . This prospective, multicenter, RCT study suggests that navigation-guided BET is a superior treatment option compared to MM alone in patients with chronic ETD.…”
Section: Discussionmentioning
confidence: 92%
“…Each patient underwent BET using both the Naviloon (balloon and guide catheter) (Mega Medical, Seoul, Korea) and the Mega Navigation (image-guided navigation system; Mega Medical, Seoul, Korea). The balloon was inflated once with sterile water to a target pressure of up to 12 atm for 2 min, deflated and then reinflated for 1 min 15 . Methods related to detailed description of this navigation guided balloon Eustachian tuboplasty are described in supplementary methods and supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were nine prospective studies (three case‐control, six cohort studies) encompassing 1336 patients with CRS and patients with CRS and ETD (CRS+ETD) 1,8–15 . There were seven studies (one RCT, four prospective case series, and two retrospective case series) including 161 patients with primary ETD 3,16–19 2122. Risk of bias assessment can be found in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Ungar et al [38] assured the safety, feasibility, and accuracy of BET as a method for treating diving-induced ETD and documented that BET can significantly reduce symptoms ETDQ-7 score and pressure-equalizing sensation in all ears, and so enables patients to resume diving. Also, Choi et al [39] concluded that Image-guided navigation balloon catheters are a potentially valuable tool, technically feasible and safe when performing BET to treat ETD and resulting in progressive decrease of ETDQ-7 scores with PO time of follow-up increase frequency of positive Valsalva maneuver at 6-m post-procedure.…”
Section: Chronic Rhinosinusitis [Crs] Especially If Associated With Nasal Polyposis [Crswnp]mentioning
confidence: 99%